(untitled) (Revista Contexto & Saúde, 2025)
This study aimed to evaluate the evidence of validity based on the internal structure of the "Kidney Transplant Understanding Tool - Brazil" (K-TUT-BR). This is a methodological study with quantitative approach in which the data collection took place through the application of a sociodemographic/clinical questionnaire and K-TUT-BR. The participants were pre-transplant renal patients or outpatient follow-up transplants. The sample consisted of 300 patients. The study was approved by the Research Ethics Committee under Opinion number 5,939,285. The data were analyzed in the software FACTOR version - 12.04.01 and JASP version 0.17.3.0. Successive exploratory factor analyses were performed for the set of items, followed by analysis of variance of the items. In this study, a 4-factor model (F1, F2, F3 and F4) was found for 11 items of the instrument under test, with good adjustment indices. The parallel analysis recommended extraction of four factors as the most representative for the data, which revealed acceptable composite reliability (greater than 0.70) for F1 and F3 factors. The overall reliability of the instrument was also acceptable (CRC=0.660). Thus, the K-TUT-BR represents an important instrument to evaluate patients’ knowledge about kidney transplantation.